The impact of adolescence initiated alcohol and cannabis abuse/ dependence on the level of activity participation in adult males suffering from a pyschotic disorder - Wolhuter, Kristyn Ashleigh (My University, 2014)
Background: Individuals suffering from both a psychotic disorder and a substance abuse disorder have shown to have poorer occupational outcomes. This study aimed at determining the exact consequences of substance abuse on occupational performance in order to tailor more specific treatment interventions in the future. Methodology: A non-experimental design and observational study was used. This involved a once off occupational therapy assessment using the Activity Participation Outcome Measure (APOM) as the recoding tool. The participants were divided into three groups: Alcohol abuse, cannabis abuse and no substance abuse. Methodology: A non-experimental design and observational study was used. This involved a once off occupational therapy assessment using the Activity Participation Outcome Measure (APOM) as the recoding tool. The participants were divided into three groups: Alcohol abuse, cannabis abuse and no substance abuse. Results: A statistically significant difference was noted between the alcohol and cannabis groups. The alcohol group achieved a higher level of activity participation in all eight APOM domains (Role performance, life skills, communication, motivation, process skills, self esteem, balanced lifestyle, and affect). The no substance abuse group (individuals diagnosed with schizophrenia) showed the lowest level of activity participation. Conclusion: Cannabis adolescent abuse/dependence appears to have a more negative impact on activity participation when compared to alcohol abuse.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg, 2014.
Keywords: Marijuana Abuse; Alcoholism; Psychotic Disorders